Comparison of pathogenic bacteria in the upper and lower respiratory tracts of cattle either directly transported to a feedlot or co-mingled at auction markets prior to feedlot placement - Hirsch, Christina; Timsit, Edouard; Uddin, Muhammed Salah; Guan, Le Luo; Alexander, Trevor W. (Frontiers in Veterinary Science, 2023)
Bacterial bronchopneumonia (BP) has been associated with purchasing cattle through auction markets. However, whether auction markets are a source of BP-associated bacterial pathogens is unknown. This study evaluated prevalence, antimicrobial susceptibility, and genetic relatedness (using pulsed-field gel electrophoresis, PFGE) of Mannheimia haemolytica, Pasteurella multocida, and Histohpilus somni isolated from cattle either transported to an auction market prior to feedlot placement (AUC), or directly to a feedlot from a farm (RANC). Two groups of cattle were enrolled (N=30 per group) from two separate farms with 15 animals from an individual farm designated as AUC or RANC. Deep nasal swab (DNS) and trans-tracheal aspirates (TTA) were collected on day 0 at weaning (T0) and on day 2 at on-arrival processing at the feedlot (T1). The DNS were also collected on day 9 (T2) and day 30 (T3) after arrival at the feedlot. In both TTA and DNS, prevalence of bacteria did not differ between AUC and RANC groups (P > 0.05). None of the bacteria isolated at T0 were resistant to antimicrobials and diversity of all bacteria was greatest at T0 and T1. In Group 1 cattle, 100% of P. multocida isolated at T2 and T3 were multi-drug resistant. These isolates were highly related (>90%) according to PFGE, with most being clones. This study showed that auction markets were not a major source of resistant BP pathogens, however, horizontal transmission of a multi-resistant strain of P. multocida occurred in a feedlot. Spread of resistant P. multocida was likely due to the selective pressures imposed by feedlot antimicrobial use and encoded resistance by the bacteria.